2019
DOI: 10.5455/medarh.2019.73.144-148
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hyperglycemia to The mRNA Level and Protein Expression of Perlecan at Rat Model of Osteoarthritis with Diabetes Mellitus Type 1

Abstract: Introduction: Previous research found that diabetes mellitus capable to aggravate osteoarthritis disease. In brief, the hyperglycemia condition in diabetes mellitus has an impact on protein glycation of all joint components, including molecule, such as perlecan. The protein expression of perlecan reflects the presence amount of perlecan in the matrix of articular cartilage. However, the impact of hyperglycemia on articular perlecan has not been explained. Moreover, the role of perlecan as a mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The study conducted by Njoto I. et al confirms that DM with characteristic perlecan expression is a trigger for OA [ 30 , 31 ]. Radojčić MR et al revealed that there are associations between the novel ECM biomarker C1M and local and systemic interleukin 6 with synovitis and pain, finding a net loss of collagen elevation and increase in levels of MMP-2, -9, and -13.…”
Section: Rheumatoid Arthritis (Ra) and T1dmmentioning
confidence: 96%
“…The study conducted by Njoto I. et al confirms that DM with characteristic perlecan expression is a trigger for OA [ 30 , 31 ]. Radojčić MR et al revealed that there are associations between the novel ECM biomarker C1M and local and systemic interleukin 6 with synovitis and pain, finding a net loss of collagen elevation and increase in levels of MMP-2, -9, and -13.…”
Section: Rheumatoid Arthritis (Ra) and T1dmmentioning
confidence: 96%
“…For example, chronic hyperglycemia has been suggested to adversely affect the functions and structures of articular cartilage, bone, tendons and ligaments, and synovium, all of which have been involved in the pathogenesis of OA [7]. Moreover, a subsequent study in rat model of OA showed that hyperglycemia increased the severity of OA via decreasing the mRNA and protein expression of perlecan [8]. Besides, a recent study in guinea pig showed that plasma glucose concentration was positively correlated with proteoglycan loss, suggesting hyperglycemic stress after rapamycin treatment was related to the deteriorated OA [9].…”
Section: Introductionmentioning
confidence: 99%